Average cross section measurement for 162Er(γ,n) reaction compared with theoretical calculations using TALYS - Vagena, E.; Stoulos, S. (HNPS Advances in Nuclear Physics, 2019)
Bremsstrahlung photon beam delivered by a linear electron accelerator has been used to experimentally determine the near threshold photonuclear cross section data of nuclides. For the first time, (γ,n) cross section data was obtained for the astrophysical important nucleus 162Er. Moreover, theoretical calculations have been applied using the TALYS 1.6 code. The effect of the gamma ray strength function on the cross section calculations has been studied. A satisfactorily reproduction of the available experimental data of photonuclear cross section at the energy region below 20 MeV could be achieved. The photon flux was monitored by measuring the photons yield from seven well known (γ, n) reactions from the threshold energy of each reaction up to the end-point energy of the photon beam used. An integrated cross-section 87 ± 14 mb is calculated for the photonuclear reaction 162Er(γ,n) at the energy 9.2 - 14 MeV. The effective cross section estimated using the TALYS code range between 89 and 96 mb depending on the γ-strength function used. The result for 162Er(γ,n), is found to be in good agreement with the theoretical values obtained by TALYS 1.6. So, the present indirect process could be a valuable tool to estimate the effective cross section of (γ,n) reaction for various isotopes using bremsstrahlung beams.